2017
DOI: 10.1371/journal.pone.0172961
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia following intravenous insulin plus glucose for hyperkalemia in patients with impaired renal function

Abstract: BackgroundHypoglycemia is a serious complication following the administration of insulin for hyperkalemia. We determined the incidence of hypoglycemia and severe hypoglycemia (blood glucose <70 or ≤40 mg/dl, respectively) in a cohort of AKI and non-dialysis dependent CKD patients who received an intravenous infusion of insulin plus glucose to treat hyperkalemia.MethodsWe retrospectively reviewed charts of all AKI and non-dialysis dependent CKD patients who received 10 U of insulin plus 50 g glucose to treat hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 34 publications
3
46
2
Order By: Relevance
“…Of the 29 unique non‐randomised interventional studies identified in this SLR, 13 investigated temporising agents and 6 ZS or organic cation‐binding agents for the management of hyperkalaemia . Twelve out of 43 unique observational studies identified in the SLR reported on management of hyperkalaemia with SPS or CPS and 11 focused on temporising agents; however, a comparison of temporising agents was not in the scope of this work, given their use in the emergency setting …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 29 unique non‐randomised interventional studies identified in this SLR, 13 investigated temporising agents and 6 ZS or organic cation‐binding agents for the management of hyperkalaemia . Twelve out of 43 unique observational studies identified in the SLR reported on management of hyperkalaemia with SPS or CPS and 11 focused on temporising agents; however, a comparison of temporising agents was not in the scope of this work, given their use in the emergency setting …”
Section: Resultsmentioning
confidence: 99%
“…[56][57][58][59][60][61] Twelve out of 43 unique observational studies identified in the SLR reported on management of hyperkalaemia with SPS or CPS 62-73 and 11 focused on temporising agents; however, a comparison of temporising agents was not in the scope of this work, given their use in the emergency setting. [74][75][76][77][78][79][80][81][82][83][84] Non-systematic or narrative reviews Case reports Commentaries and editorials SLRs or network meta-analyses (NMAs) of relevant studies were included at title/abstract review stage for the purpose of identifying any additional studies not identified in the database searches, but subsequently excluded at full-text review stage…”
Section: Identified Evidence On Hyperkalaemia Managementmentioning
confidence: 99%
“…The reported incidence in hospitalized patients ranges from 6% to 75% depending on the population studied, the doses of insulin/ dextrose administered, and the definition of hypoglycemia. [5][6][7][8] Hypoglycemia itself is associated with increased morbidity and mortality in hospitalized patients. 9 The aims of this study were to describe the incidence of hypoglycemia following hyperkalemia treatment with intra-venous insulin/dextrose in inpatients in a large (900-bed) UK teaching hospital and to determine the risk factors predisposing to hypoglycemia.…”
mentioning
confidence: 99%
“…Prior studies have likely underestimated the incidence of hyperkalemia treatment-associated hypoglycemia as glucose levels are rarely checked within three hours of insulin administration. 8 In our study, which was designed to ensure appropriate blood glucose measurement, 21% of insulin treatments for hyperkalemia resulted in hypoglycemia, with 92% of hypoglycemic events occurring within the first three hours.…”
Section: Discussionmentioning
confidence: 99%